ANALISIS PELAKSANAAN PROGRAM EKSTRAKURIKULER DALAM MENGEMBANGKAN MINAT DAN BAKAT DI MTs PAB 2 SAMPALI - Laila Salsabina S; Abdul Fattah Nasution; Malika Aulia Husnah S; Rizqi Almaajid (Cendekia Madani Nusantara, 2024)
ABSTRACT This research analyzes the effectiveness of implementing extracurricular programs in developing students' interests and talents. With a qualitative descriptive approach and involving interviews, observation, and documentation, this research found that successful programs have clear goals, active student participation, and consistent support from parents and teachers. The program provides space for exploratory interests, builds additional skills, and increases student engagement. These findings highlight the importance of designing extracurricular programs that are inclusive, diverse, and focus on the unique potential of each student, by instilling positivity in elementary school development. This analysis shows that implementing effective extracurricular programs allows students to grow and develop holistically, including aspects of interests and talents that may not be fully explored in the academic curriculum. Extracurricular programs also help improve students' social, communication and work skills. However, this analysis also found several challenges faced in implementing extracurricular programs, such as lack of funding, lack of facilities and guaranteed student participation.